Formulation of Definitions of Consciousness on the Methodological Basis of Realism - Diržys, Adas (Problemos, 2022)
In this paper, the traditional question – what is mind? – is suggested to be treated from the metareflective realist stance from which different determinations of consciousness could be apprehended as always instantiated and dependent on their definitions. Methodological differentiation between what is representational and what is non-representational is expressed as a divergence between particular definitions of consciousness and the ontological X, in this context, acting as a universality of consciousness. The derivation of this position is reached through the investigation of François Laruelle’s non-standard philosophy, Wilfrid Sellars’s critique of the myth of the given and Iain Hamilton Grant’s revisionary study of Schelling’s naturphilosophie.